Fe3O4 (at) PDA-MnO2 nano material as well as preparation method and application thereof
By developing the combination of Fe3O4@PDA-MnO2 nanomaterials and nanoenzyme-photothermal therapy, the drug resistance and probiotic reduction problems in the treatment of BV were solved, and the antibacterial effect was achieved with high efficiency and low toxicity, and the vaginal microecological environment was improved.
Patent Information
- Application Number
- CN202510174495.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-18
AI Technical Summary
In the prior art In the treatment of bacterial vaginosis (BV), antibiotic treatment can easily lead to bacterial resistance and reduced vaginal probiotics, resulting in high recurrence rates and negatively affecting the vaginal microecological environment.
A nanomaterial of iron ion-polydopamine-coordinated MnO2 (Fe3O4@PDA-MnO2) combined with nanoenzyme-photothermal therapy (NPT), the catalytic activity is enhanced under near-infrared light irradiation, excellent photothermal properties and simulated peroxidase activity, which can effectively sterilize and destroy bacterial biofilms.
Fe3O4@PDA-MnO2 nanomaterials showed high bactericidal rate and biofilm damage ability to a variety of pathogenic bacteria under NIR irradiation, significantly reducing vaginal inflammation of BV, and better than traditional antibiotic treatment, reducing the impact on vaginal probiotics.
Smart Images

Figure CN119633114A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedicine technology, and specifically relates to a Fe3O4@PDA-MnO2 nanomaterial and a preparation method and application thereof. Background Art
[0002] Bacterial vaginosis (BV) affects up to 29% of women worldwide. It is characterized by dysbiosis of vaginal flora, a decrease in the number of probiotics (Lactobacillus) and an increase in the number of pathogenic bacteria, which leads to increased vaginal discharge and a "fishy" odor, which has a serious impact on women's health and quality of life. Untreated BV can lead to early spontaneous abortion and increase susceptibility to sexually transmitted infections. The pathogenesis of BV is multifactorial, and the factors that affect the risk of BV can be divided into four categories: intrinsic factors (race and genetics), sexual activity (sexual partners, sexually transmitted infections, condom use), hormones (menstrual cycle, intrauterine contraceptive devices, estrogen levels, oral contraceptives) and lifestyle. At present, the standard treatment for BV is oral or vaginal administration of antibiotics, usually metronidazole or clindamycin, with a high recurrence rate of 20% to 30% one month after the initial treatment and 58% after 12 months. Since the use of the above drugs will lead to a decrease in probiotics (Lactobacillus) in the vagina, BV is prone to recurrence. At the same time, antibiotic resistance is also one of the main reasons for the poor treatment effect of BV. In order to solve the problem of BV treatment, it is urgent to develop new antibacterial alternatives with different bactericidal mechanisms from traditional antibiotics, overcome bacterial resistance, and do not affect the population abundance of probiotics (Lactobacillus) in the vagina and the vaginal microecological environment.
[0003] Nanozymes, nanomaterials with enzyme-mimicking catalytic properties, have recently emerged as a new type of antimicrobial therapeutic agent, which can effectively destroy bacterial biofilms mainly by relying on their unique ability to produce toxic products. Among the various treatment options, nanoenzyme photothermal therapy (NPT) shows great potential for application in anti-infection treatment. It can overcome drug resistance, reduce drug dosage, and avoid potential systemic side effects. It is considered to be a promising alternative strategy for antibiotic treatment to fight infection. During the anti-infection treatment process, the nanoenzyme-photothermal antibacterial platform can catalyze low concentrations of exogenous hydrogen peroxide (H2O2) to produce highly toxic hydroxyl radicals (·OH), leading to protein denaturation of cell membranes. Once near-infrared (NIR) light is introduced, the nanoenzyme-photothermal antibacterial platform can quickly convert light energy into heat energy at the infection site, play the role of a "nano knife", and further cause the death of damaged bacteria through physical cutting. By utilizing the synergistic effect between the nanocatalytic activity and photothermal effect of nanoenzyme-photothermal agents, NPT can achieve excellent anti-infection treatment effects by quickly and effectively killing pathogens. Summary of the invention
[0004] In order to overcome the problems existing in the background technology, the present invention designs an iron ion-polydopamine coordinated loaded MnO2 (Fe3O4@PDA-MnO2) nanomaterial, which exhibits excellent photothermal performance and simulated peroxidase (POD) activity, and the catalytic activity is enhanced under NIR irradiation. Fe3O4@PDA-MnO2 has satisfactory bactericidal and biofilm-destroying properties against Gram-positive bacteria, Gram-negative bacteria, and Gram-mutant bacteria. The material can be combined with near-infrared (NIR) nanozyme-photothermal therapy for the treatment of bacterial vaginosis (BV).
[0005] To achieve the above object, the present invention is implemented through the following technical solutions: The preparation method of the Fe3O4@PDA-MnO2 nanomaterial comprises the following steps: (1) Mix ethylene glycol and deionized water, then add ammonia water and mix thoroughly; (2) adding dopamine solution to the mixed solution of step (1) and stirring evenly; (3) Slowly add the ferric nitrate solution dropwise into step (2) and react at 50-70° C. for 12-15 h; the molar ratio of dopamine to ferric nitrate is 1:5-7.
[0006] (4) cooling and centrifuging, washing with ethanol and water alternately for 3-4 times, and vacuum drying to obtain Fe3O4@PDA nanomaterials; (5) The Fe3O4@PDA and KMnO4 prepared in step (4) were ultrasonically dispersed in deionized water (the mass ratio of Fe3O4@PDA and KMnO4 was 1:1-1.5), then stirred at room temperature for 1-1.5 h, centrifuged, and washed with deionized water for 3-4 times. After vacuum drying, Fe3O4@PDA-MnO2 nanomaterials were obtained.
[0007] The present invention also includes Fe3O4@PDA-MnO2 nanomaterials obtained by the above preparation method.
[0008] The Fe3O4@PDA-MnO2 nanomaterial of the present invention is used in preparing a medicine for treating vaginitis.
[0009] The present invention also provides a hydrogel comprising Fe3O4@PDA-MnO2 nanomaterials.
[0010] The method for preparing the hydrogel containing Fe3O4@PDA-MnO2 nanomaterial comprises the following steps: (1) Dissolve 0.5-1.0 g chitosan in 10-15 mL 1% acetic acid aqueous solution, add 10-20 mg Fe3O4@PDA-MnO2, and stir for 10-20 min to prepare solution A. (2) Add 0.6-0.8 g of sodium alginate to 12-15 mL of propylene glycol and stir for 1-1.5 hours to prepare solution B. (3) Mix solution A and solution B, add 200-300 μL of 20 mg / mL calcium chloride solution while stirring, and continue stirring for 10-20 min to obtain Fe3O4@PDA-MnO2 hydrogel.
[0011] The hydrogel is used as a medicine for treating vaginitis.
[0012] Beneficial effects of the present invention: The Fe3O4@PDA-MnO2 nanomaterial synthesized in the present invention has excellent peroxidase-like activity and photothermal performance. Under near-infrared irradiation, the peroxidase-like activity of Fe3O4@PDA-MnO2 is greatly improved. The concentration of Fe3O4@PDA-MnO2 is 20 μg / mL and the photothermal performance is 1.0 W / cm 2 When irradiated with 808nm NIR for 10 min, the sterilization rate of Gram-positive bacteria, Gram-negative bacteria and Gram-mutant bacteria is greater than 99%, and biofilm formation is destroyed, with good biocompatibility and low toxicity.
[0013] In vitro and BV mouse model experiments showed that Fe3O4@PDA-MnO2 hydrogel combined with NIR irradiation significantly reduced vaginal inflammation caused by bacterial infection of BV due to its synergistic antibacterial effect, and was superior to the positive control drug metronidazole. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 TEM image of Fe3O4@PDA-MnO2 prepared in the present invention; Figure 2 High-resolution XPS spectra of (a) Fe 2p and (b) Mn 2p of Fe3O4@PDA-MnO2 prepared in the present invention; Figure 3 is the UV absorption spectra of Fe3O4@PDA-MnO2 with different concentrations; Figure 4 For different concentrations of Fe3O4@PDA-MnO2, 1.0 W / cm 2 , irradiate at 808 nm for 10 min, and obtain the temperature-time curve; Figure 5 Fe3O4@PDA-MnO2 (100 μg / mL) at 1.0 W / cm 2 , infrared thermal image under 808 nm irradiation; Figure 6 Fe3O4@PDA-MnO2+H2O2+TMB at 1.0 W / cm 2 , UV absorption spectra comparison of 808 nm UV light irradiation for 10 min, natural light irradiation and no irradiation; Figure 7 is the Michaelis-Menten equation of Fe3O4@PDA-MnO2 under fixed H2O2 and no light; Figure 8 is the Michaelis-Menten equation of Fe3O4@PDA-MnO2 under fixed TMB without light; Fig. 9 The Michaelis equation of Fe3O4@PDA-MnO2 under fixed H2O2 and light (1.0 W / cm 2 , 808 nm irradiation for 10 min); Fig.10 The Michaelis equation of Fe3O4@PDA-MnO2 under fixed TMB and light (1.0 W / cm 2 , 808 nm irradiation for 10 min); Fig.11 Effects of different concentrations of Fe3O4@PDA-MnO2 on the survival rates of HUVECs and Hep G2 cells at 24 h and 48 h; Fig.12The antibacterial properties of different groups of Fe3O4@PDA-MnO2 on different pathogenic bacteria under 808 nm infrared light irradiation and without irradiation; I: blank control group; II: Fe3O4@PDA-MnO2; III: Fe3O4@PDA-MnO2+ H2O2; IV: Fe3O4@PDA-MnO2+ H2O2+ NIR; Fig.13 To evaluate the anti-biofilm activity of Fe3O4@PDA-MnO2 against different pathogenic bacteria under 808 nm infrared light irradiation and without irradiation by CV staining method; Fig.14 The antibacterial SEM images of Fe3O4@PDA-MnO2 on different pathogens under 808 nm infrared light irradiation; where: I is the SEM image of various pathogens; II is Fe3O4@PDA-MnO2+ H2O2+ NIR; Fig.15 For this Example 2, mice G. vaginalis Nanozyme gel treatment effect of vaginitis model, where: I is the healthy group; II is the blank group; III is the Fe3O4@PDA-MnO2 hydrogel treatment group; IV is the Fe3O4@PDA-MnO2 hydrogel + H2O2 treatment group; V is the Fe3O4@PDA-MnO2 hydrogel + H2O2 + NIR treatment group; VI is the metronidazole treatment group; Fig.16 The following is a diagram showing the changes in the appearance of the reproductive system of mice in each group in Example 2. Groups I to VI are the same. Fig.12 ; Fig.17 The graphs of changes in inflammatory cytokines in mice in each group before and after nanozyme gel treatment in Example 2 are shown in Figures 1 to 6. Fig.15 ; Fig.18 This is the histopathological staining image of the mouse model of vaginitis in Example 2, where: I is the healthy group; II is the blank group; II is the Fe3O4@PDA-MnO2 hydrogel+H2O2+NIRI treatment group. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0016] The preparation method of the iron ion-polydopamine coordinated loaded MnO2 (Fe3O4@PDA-MnO2) nanomaterial comprises the following steps: (1) Mix 16-20 mL of ethylene glycol with 10-12 mL of deionized water, add 3-4 mL of 28% ammonia water by volume, stir at 60°C for 10-15 min, add 10-15 mL of 50 mg / mL dopamine solution, stir evenly, then slowly drop 10-15 mL of 18 mg / mL Fe(NO3)3·9H2O into the mixed solution, react at 60°C for 12-15 h, cool and centrifuge, wash alternately with ethanol and water for 3-4 times, and vacuum dry to obtain Fe3O4@PDA nanomaterials; (2) ultrasonically dispersing 100-150 mg of Fe3O4@PDA and 100-150 mg of KMnO4 prepared in step (1) in 25-40 mL of deionized water, stirring at room temperature for 1-1.5 h, centrifuging, washing with deionized water for 3-4 times, and vacuum drying to obtain Fe3O4@PDA-MnO2 nanozyme; (3) Dissolve 0.5-1.0 g chitosan in 10-15 mL 1% acetic acid aqueous solution by stirring, add 10-20 mg Fe3O4@PDA-MnO2, and stir for 10-20 min to prepare liquid A; add 0.6-0.8 g sodium alginate into 12-15 mL propylene glycol and stir for 1-1.5 h to prepare liquid B; mix liquid A and liquid B, add 200-300 μL of 20 mg / mL calcium chloride solution while stirring, and continue stirring for 10-20 min to obtain Fe3O4@PDA-MnO2 hydrogel.
[0017] In order to more clearly illustrate the present invention, it is described in detail through the following examples.
[0018] Example 1
[0019] The preparation method of iron ion-polydopamine coordinated loaded MnO2 (Fe3O4@PDA-MnO2) nanomaterial comprises the following steps: (1) Mix 16 mL of ethylene glycol with 12 mL of deionized water, add 3-4 mL of 28% by volume ammonia water, stir at 60°C for 15 min, add 12 mL of 50 mg / mL dopamine solution, stir evenly, then slowly drop 12 mL of 18 mg / mL Fe(NO3)3·9H2O into the mixed solution, react at 60°C for 12 h, cool and centrifuge, wash alternately with ethanol and water for 3 times, and vacuum dry to obtain Fe3O4@PDA nanomaterials.
[0020] (2) Take 150 mg of Fe3O4@PDA and 150 mg of KMnO4 prepared in step (1) and ultrasonically disperse them in 40 mL of deionized water. Then stir them at room temperature for 1.2 h, centrifuge them, and wash them with deionized water three times. After vacuum drying, Fe3O4@PDA-MnO2 nanomaterials were obtained.
[0021] Figure 1 This is the TEM image of Fe3O4@PDA-MnO2 obtained in this example. The TEM image shows that the Fe3O4@PDA-MnO2 nanomaterial has a chrysanthemum-like morphology with an average diameter of 50~100 nm.
[0022] Figure 2 High-resolution XPS spectra of (a) Fe 2p and (b) Mn 2p of Fe3O4@PDA-MnO2. 3 / 2 and Fe2p 1 / 2 710.1 eV (Fe 2+ ) and 723.5 eV (Fe 3+ ) determined Fe 2+ and Fe 3+ coexistence Figure 2 a); high-resolution Mn 2p spectrum ( Figure 2 Figure b) shows two peaks at 640.9 and 652.9 eV, corresponding to the Mn 2p 3 / 2 and Mn 2p 1 / 2 , indicating the formation of manganese dioxide.
[0023] Evaluation of photothermal performance of Fe3O4@PDA-MnO2 nanomaterials: In order to evaluate the NIR-triggered photothermal properties of Fe3O4@PDA-MnO2 nanomaterials, the temperature change of the nanomaterial solution under 808 nm NIR laser irradiation was measured. The UV-visible absorption spectra of Fe3O4@PDA-MnO2 solutions with different concentrations were detected (see Figure 3 ),Depend on Figure 3It can be seen that with the increase of the concentration of Fe3O4@PDA-MnO2 nanomaterials (0 ~ 200μg / mL), the absorbance at 808nm (0.001 ~ 0.921) increased accordingly. This result shows that the absorption of near-infrared light (808nm) by Fe3O4@PDA-MnO2 is concentration-dependent, which prompted us to further explore the photothermal properties of Fe3O4@PDA-MnO2 at different concentrations. Next, we continued to study the photothermal effect of Fe3O4@PDA-MnO2 because of its enhanced absorption in the near-infrared region. As expected, the temperature of Fe3O4@PDA-MnO2 (200 μg / mL) increased significantly from 22.6℃ to 62.2℃, and was positively correlated with the concentration, while water only increased by 6.9℃ ( Figure 4 At the same time, the temperature change of the nanozyme solution under 808 nm near-infrared laser irradiation was monitored by an infrared thermal imaging camera (see Appendix Figure 5 ). The experimental results show that the temperature change in Fe3O4@PDA-MnO2 (200 μg / mL) depends on the time gradient, and the temperature reaches 64.8℃ within 10min.
[0024] Evaluation of Fe3O4@PDA-MnO2 peroxidase nanozyme activity: TMB was used as the catalytic reaction substrate to evaluate its peroxidase-like activity. 100 μL of 5 mmol / L TMB, 100 μL of 50 mmol / L H2O2 and 10 μL of 1 mg / mL Fe3O4@PDA-MnO2 were added to a 5 mL stoppered colorimetric tube, and then 2.79 mL of NaAc-HAc buffer solution (pH 4.0) was added. The mixture was thoroughly mixed and the volume was adjusted to 3 mL. The absorbance was measured after 10 min of reaction. At the same time, the experiment was carried out under the same conditions without light, natural light and 1.0 W / cm 2 The enzyme activity after irradiation with 808 nm infrared light for 10 min was compared, and the absorbance was measured at 654 nm. The results are as follows Figure 6 Compared with no irradiation under 808 nm near-infrared light, irradiation under near-infrared light significantly enhanced the peroxidase activity of Fe3O4@PDA-MnO2, and Fe3O4@PDA-MnO2 exhibited the characteristics of near-infrared light-enhanced peroxidase activity.
[0025] The experiment also carried out the determination of Michaelis-Menten catalytic kinetic parameters under natural light irradiation: fixed H2O2, changing TMB concentration; fixed TMB, changing H2O2 concentration; 2 , 808 nm infrared light irradiation: fix H2O2, change TMB concentration; fix TMB, change H2O2 concentration, the results are as follows Figures 7 to 10 As shown in Table 1. Michaelis constants of Fe3O4@PDA-MnO2 for substrates TMB and H2O2 K m The values of NH4Cl and NH4Cl were 0.98 mmol / L and 1.48 mmol / L respectively, and the reaction rate constant was 0.45×10 -6 mol / L min and 0.12×10 -6 mol / L min, after infrared light irradiation K m is 0.20 mmol / L and 1.47 mmol / L, and the reaction rate constant is 5.79×10 -6 mol / L min and 4.05×10 -6 mol / L min, indicating that infrared light irradiation increased the affinity and reaction rate of Fe3O4@PDA-MnO2 nanozyme with the substrate.
[0026] Table 1 Michaelis-Menten catalytic kinetic parameters
[0027] Cytotoxicity test: The CCK-8 cell viability kit was used to detect the cytotoxicity of the nanozyme. In the specific experiment, human umbilical vein endothelial cells and hepatoma cells (HUVECs and Hep G2, Beina Chuanglian Biotechnology Co., Ltd.) were inoculated in 96-well plates and cultured for 24 h. They were then incubated with different concentrations of Fe3O4@PDA-MnO2 for 24 h and 48 h, respectively. The cells were rinsed with PBS in batches, and CCK-8 solution was added to each well to a concentration of 10%. The cells were incubated at 37°C and the absorbance was measured at 450 nm. CCK-8 analysis ( Fig.11 ) showed that Fe3O4@PDA-MnO2 had no toxicity to cells.
[0028] Fe3O4@PDA-MnO2 antibacterial test: The strains used in the experiment were obtained from Beina Chuanglian Biotechnology Co., Ltd.
[0029] Experimental method: Staphylococcus aureus ( S. aureus , ATCC 43300), methicillin-resistant Staphylococcus aureus (MRSA, ATCC-6538), Escherichia coli ( E. coli , ATCC-8099), ampicillin-resistant Escherichia coli ( E. coli , SHBCC D25148) are representative of Gram-positive, Gram-negative strains and Gram-variants ( G. vaginalisThe antibacterial properties of Fe3O4@PDA-MnO2 were determined by counting the number of CFU using the plate counting method. First, the above-mentioned strains were incubated in solid Luria-Bertani (LB) medium and solid nutrient broth medium for 24 h. A small amount of colonies formed were picked up with an inoculation loop and inoculated into liquid culture medium (5 mL). Then, the bacterial suspension (1×10) was obtained after shaking and incubating at 37°C and 180 rpm in a constant temperature shaker for 12 h. 8 CFU / mL), diluted to 1×10 5 CFU / mL.
[0030] The materials were divided into four groups: blank control group, Fe3O4@PDA-MnO2, Fe3O4@PDA-MnO2+H2O2, and Fe3O4@PDA-MnO2+H2O2+NIR groups, where the concentration of Fe3O4@PDA-MnO2 was 20 μg / mL and the concentration of H2O2 was 50 mmol / L. The cultured bacteria were added to phosphate buffer as the blank control group and then exposed to 1.0 W / cm 2 , 808 nm irradiation for 10 min or without infrared light irradiation, incubated at 37°C for 60 min, the bacterial suspension was diluted (100 μL) and evenly spread on LB solid medium and nutrient broth solid medium, cultured at 37°C for 24 h, the colony count was calculated, and the antibacterial activity was determined; SEM characterization was performed (see Appendix Fig.12 , I is the blank control group, II is the Fe3O4@PDA-MnO2 group, III is the Fe3O4@PDA-MnO2+H2O2 group, and IV is the Fe3O4@PDA-MnO2+H2O2+NIR group). The results showed that the blank control group had almost no antibacterial properties, but under 20 min of NIR irradiation, it showed excellent antibacterial effects against all bacteria, with a nearly 100% bactericidal rate against all bacteria. The control group retained complete cell morphology. However, in the presence of NIR or H2O2, the cell membranes of AREC, MRSA, and Gardnerella vaginalis showed wrinkles and shrinkage, while the cells were completely destroyed after Fe3O4@PDA-MnO2+H2O2+NIR treatment.
[0031] To further evaluate the antibacterial properties of Fe3O4@PDA-MnO2, we investigated its anti-biofilm ability by crystal violet (CV) staining and measured the absorbance at 590 nm to quantify the biofilm. The formation of biofilm was clearly observed in the control group, and Fe3O4@PDA-MnO2+H2O2+NIR significantly inhibited the formation of bacterial biofilm after incubation for 48 h ( Fig.13 ), showing the lowest biofilm survival rate of 27.9 %.
[0032] In order to further determine the antibacterial ability of Fe3O4@PDA-MnO2, AREC, MRSA, E . coli and S . aureus SEM observation ( Fig.14 , I is the blank control group, II is the Fe3O4@PDA-MnO2+H2O2+NIR treatment group), the results showed that the control group retained complete cell morphology. However, AREC, MRSA, E . coli and S . aureus The cell membrane becomes wrinkled, shrunken, completely ruptured or even loses its original shape.
[0033] Example 2
[0034] Preparation method of Fe3O4@PDA-MnO2 nanomaterial hydrogel 1.0 g of chitosan was dissolved in 15 mL of 1% acetic acid aqueous solution by stirring, and 20 mg of Fe3O4@PDA-MnO2 was added and stirred for 15 min to prepare liquid A. 0.6-0.8 g of sodium alginate was added to 14 mL of propylene glycol and stirred for 1.5 h to prepare liquid B. Liquid A and liquid B were mixed, and 280 μL of 20 mg / mL calcium chloride solution was added while stirring, and stirring was continued for 10 min to obtain Fe3O4@PDA-MnO2 hydrogel.
[0035] Construction of mouse BV model and anti-inflammatory effect test: Mouse BV model: All animal experiments were conducted in accordance with the Animal Care Guidelines. Female ICR mice aged 10 weeks and weighing 18-20 g were selected as experimental animals and randomly divided into 4 groups, with 8 mice in each group. For the vaginitis model, mice received a subcutaneous injection of 0.5 mg of 17β-estradiol. Three days after the injection, 20 μL of vaginal inoculation was performed. G. vaginalis (About 5.0×10 8 CFU / mL) bacterial suspension once a day for 3 consecutive days to infect mice. After infection, different treatment methods were used: I was the healthy group; II was the infected group (blank control group without any treatment); III was the Fe3O4@PDA-MnO2 hydrogel treatment group (50 μL); IV was the Fe3O4@PDA-MnO2 hydrogel (50 μL) + H2O2 (10 μL) treatment group; V was the Fe3O4@PDA-MnO2 hydrogel (50 μL) + H2O2 (10 μL) + NIR treatment group (1.0 W / cm 2, 808 nm infrared light irradiation); VI was the metronidazole treatment group (10 μL).
[0036] Evaluation of changes in swelling of mouse vaginitis: After 10 days of treatment, the vagina of the blank group was significantly swollen (see Fig.15 Among them, the right picture is the plate count corresponding to the plate smeared with vaginal secretions after washing with PBS). The swelling of the Fe3O4@PDA-MnO2 hydrogel + H2O2 group was reduced, the swelling of the metronidazole group was reduced, and the Fe3O4@PDA-MnO2 hydrogel + H2O2 + NIR had no edema at all, and the vagina also contracted to normal.
[0037] Changes in the appearance of the reproductive system such as Fig.16 The vagina, cervix, "Y"-shaped uterus and ovaries of BV mice showed varying degrees of congestion, redness and swelling. The vagina was longitudinally dissected and purulent, bloody or purulent secretions were found in the vagina. After 10 days of treatment, Fe3O4@PDA-MnO2 hydrogel The redness and swelling of the reproductive system structure of mice in the +H2O2+NIR group were significantly reduced compared with those in other groups.
[0038] ELISA to detect IL-6 and TNF-α levels: After the last administration, the mice were fasted but not watered for 12 h, and peripheral blood was collected from the vaginal tissues of the mice. ELISA was used to detect IL-6 and TNF-α in the plasma of each group of mice. The results showed that ( Fig.17 , I-VI groups are the same Fig.15 ), after 5 days of treatment, the levels of inflammatory cytokines IL-6 and TNF-α in the vaginal tissue of Fe3O4@PDA-MnO2 hydrogel+H2O2+NIR were significantly lower than those in the other groups and the blank group (P<0. 05).
[0039] Meanwhile, infected BV tissues (heart, liver, spleen, lung, kidney, vagina, and uterus) were harvested on day 10 and first subjected to H&E staining to evaluate the pathological changes in the tissues, e.g. Fig.18 As shown (I is the healthy group, II is the blank group, and III is the Fe3O4@PDA-MnO2 hydrogel + H2O2 + NIRI group). The results showed that mice treated with Fe3O4@PDA-MnO2 hydrogel + H2O2 + NIR showed no obvious tissue damage and lesions in the seven major tissues, which was consistent with the healthy group, indicating that the treatment method has good biosafety.
[0040] The above results indicate that the nanozyme Fe3O4@PDA-MnO2 prepared by the present invention has peroxidase-like activity and infrared photothermal properties. The nanozyme simulates the peroxidase activity and photothermal properties to jointly exert antibacterial effects, and has an effective anti-inflammatory effect on bacterial vaginitis in mice.
[0041] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for preparing Fe3O4@PDA-MnO2 nanomaterial, characterized in that: The following steps are involved: (1) Mix ethylene glycol and deionized water, then add ammonia water and mix thoroughly; (2) adding dopamine solution to the mixed solution of step (1) and stirring evenly; (3) Slowly add the ferric nitrate solution dropwise into step (2) and react at 50-70°C for 12-15 hours; (4) cooling and centrifuging, washing with ethanol and water alternately for 3-4 times, and vacuum drying to obtain Fe3O4@PDA nanomaterials; (5) The Fe3O4@PDA and KMnO4 prepared in step (4) were ultrasonically dispersed in deionized water, and then stirred at room temperature for 1-1.5 h, centrifuged, and washed with deionized water for 3-4 times, and vacuum dried to obtain Fe3O4@PDA-MnO2 nanomaterials.
2. The Fe3O4@PDA-MnO2 nanomaterial obtained by the preparation method as claimed in claim 1.
3. Use of the Fe3O4@PDA-MnO2 nanomaterial as described in claim 2 in the preparation of a drug for treating vaginitis.
4. A hydrogel comprising the Fe3O4@PDA-MnO2 nanomaterial as claimed in claim 2.
5. A method for preparing a hydrogel comprising the Fe3O4@PDA-MnO2 nanomaterial as claimed in claim 2, characterized in that: The following steps are involved: (1) Dissolve 0.5-1.0 g chitosan in 10-15 mL 1% acetic acid aqueous solution, add 10-20 mg Fe3O4@PDA-MnO2, and stir for 10-20 min to prepare solution A. (2) Add 0.6-0.8 g of sodium alginate to 12-15 mL of propylene glycol and stir for 1-1.5 h to prepare solution B. (3) Mix solution A and solution B, add 200-300 μL of 20 mg / mL calcium chloride solution while stirring, and continue stirring for 10-20 min to obtain Fe3O4@PDA-MnO2 hydrogel.
6. Use of the hydrogel according to claim 4 in preparing a vaginitis medicament.
Citation Information
Patent Citations
Preparation of Fe3O4@PDA@MnO2 core-shell nanoparticles and enrichment and electrochemical detection of heavy metal ions
CN111007123A
Nano enzyme-probiotic compound as well as preparation method and application thereof
CN115590888A
Cationic nano-enzyme as well as preparation method and application thereof
CN118806790A
Composite hydrogel as well as preparation method and application thereof
CN119405877A
Cited By
Ointment for treating senile vulva lichen sclerosus and preparation method thereof
CN120267728A